HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN DENGAN PERILAKU KELUARGA SADAR GIZI (KADARZI) PADA MASYARAKAT PERKOTAAN DAN PERDESAAN DI KABUPATEN BANYUMAS - Rahardjo, Setiyowati; Kusuma Wati, Erna (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT KADARZI is a family that is able to identify nutritional problem and is able to prevent and address the nutritional problems of each family member (Ministry Of Health,2004). The purpose of this study was to determine the relationship of education and knowledge level of mothers with nutrition conscious family behavior (KADARZI) in urban and rural communities Banyumas district. This study is a secondary data analysis of KADARZI survey in 2009 conducted by the District Health Office Banyumas using cross sectional design. The sample is part of the Head of the Family in East Purwokerto District and Kembaran District with a total number of households was 600 taken with Cluster Random Sampling method. Data analysis was done using univariate and bivariate with chi square test. From the analysis on the results : majority of households (69.7%) ,low nutritional knowledge (54.7%) and has KADARZI behavior that is still less  (68.7%). While the majority of respondens in urban areas (56.3%) have high educated level (51.3%) and has KADARZI behavior that is still less (66 %). There is a relationship between education and knowledge with KADARZI behavior in rural areas represented by Kembaran I district. There was no correlation between education with KADARZI behavior in urban areas are represented by East Purwokerto. There is relationship between education and behavior KADARZI in East Purwokerto. Needs to be increased active participation of families in various health service activities such as regular weighing under five every month, actively participates in outreach activities Keywords : KADARZI, rural,urban  Kesmasindo. Volume 4,  Nomor 2, Juli 2011, hlm. 150-158